Pharmacological potential of natural chalcones: a recent studies and future perspective - Adhikari, Suman; Nath, Priyatosh; Deb, Vishal Kumar; Das, Niranjan; Banerjee, Antara; Pathak, Surajit; Duttaroy, Asim K. (Frontiers in Pharmacology, 2025)
Chalcones isolated from natural sources are the primary metabolites of numerous biologically intriguing and pharmacologically essential drugs. Chalcones’ pharmacological properties are believed to result from a double bond conjugated to carbonyl functionality. This review aims to summarise the research findings, showing naturally occurring chalcones as a preferred scaffold in medicinal chemistry. Natural chalcones have an intense antimicrobial activity that targets many pathogens, including viruses, bacteria, fungi, and protozoa. Strong antibiotic qualities are exhibited by chalcones, including 4-hydroxyderricin, licochalcone A and C, isobavachalcone, and pinocembrin chalcone. Furthermore, chalcones are promising pharmacological agents for cancer treatment; they inhibit angiogenesis, decrease metastasis, and induce death in tumor cells via diverse mechanisms. Chalcones are also considered promising therapeutic agents for diabetes, neurodegenerative diseases, and cardiovascular diseases because of their anti-inflammatory and antioxidant characteristics and ability to modify enzyme functioning. This review emphasizes several aspects, such as the biosynthesis of chalcones, preparation of chalcone derivatives, isolation of chalcones, structural features of chalcones, structure-activity relationship study, the role of natural chalcones in managing various diseases and illustrates their action mechanism to control disease progression.